Dór, ión, kalotaszegi: A debreceni egyetemi református templom tervpályázata, 1938 - Veress, Dániel (Studia Litteraria, 2021)
The University of Debrecen, together with the first Hungarian university faculty of reformed theology, was founded in 1912. The institute relocated to its new campus in 1932, and there had also been plans for the erection of a university church, which was finally completed in 1942 by architect József Borsos. This study focuses on the 1938 design competition for the university church which re-emerged recently when a significant part of the submitted entries was discovered in the collection of the local church district’s library. Due to this discovery, along with the winning design of Borsos, the two further awarded and the three purchased entries have also come to light. This study’s primary aim is to publish the blueprints that had been unknown up until recently. Additionally, I attempted to position the competition entries in the context of the religious architectural history of interwar Hungary; as well as to compare the ideas of the architects and the clients. During the exploration of the competition’s history, I considered the following question to be the most relevant one: Was there any chance that the university of a city often called the “Calvinist Rome” would have a church built in any other style than “classicizing modernism” in interwar Hungary?